Requirement of NF-kappaB signalling pathway for modulation of the cholinergic muscarinic M3 receptor expression by INGAP-PP in insulin-producing cells - Paula, Flavia M.M. (2010)
The pentadecapeptide comprising the 104–118 amino acid sequence of the ilotropin-derived Reg3-related islet neogenesis-associated protein (INGAP-PP) has been implicated in beta cell neogenesis and enhancement of insulin secretion in pancreatic islets. The aim of this study was to investigate intracellular pathways by which INGAP-PP signals in insulin-producing cells. Treatment with INGAP-PP increased insulin secretion and intracellular calcium levels in MIN6 cells. INGAP-PP exposure activated c-Myc, serum and particularly nuclear factor-kappaB (NF-κB) response elements in insulin-producing cells (1.7 ± 0.1, 1.8 ± 0.1, 2.4 ± 0.3 for RINm5F, and 1.3 ± 0.1, 1.3 ± 0.1 and 1.6 ± 0.1 fold for MIN6 cells compared to controls, respectively). There was an increase in the proliferation rate of viable cells (162 ± 17% for RINm5F and 155 ± 13% for MIN6) that was accompanied by an increase in proliferating cell nuclear antigen (PCNA) protein expression (187 ± 19% and 170 ± 8% for RINm5F and MIN6 cells respectively) following INGAP-PP treatment. INGAP-PP increased the expression of the muscarinic M3 receptor subtype (169 ± 4% for RINm5F and 222 ± 20% for MIN6 cells). Activation of multiple serum response elements by foetal calf serum also increased muscarinic M3 receptor expression (173 ± 9% for RINm5F and 140 ± 7% for MIN6 cells). The blockade of NF-κB signalling pathway strongly decreased muscarinic M3 receptor expression in response to both stimuli. In summary, a network of intracellular signals that includes activation of c-Myc signalling pathway and increased PCNA expression might be related to the increased proliferation rate of insulin-producing cells following incubation with INGAP-PP. NF-κB signalling plays an essential role in controlling the expression of the muscarinic M3 receptor.